HUBUNGAN KARAKTERISTIK PEKERJA DAN PEKERJAAN DENGAN KELUHAN MUSCULOSKELETAL DISORDER (MSDS) PADA PEKERJA BAGIAN MOBILE EQUIPMENT MAINTENANCE (MEM) PT VALE INDONESIA - MUHAMMAD RIZKI SEPTRIANTO (JURNAL PENELITIAN KESEHATAN, 2017)
Mobile Equipment Maintenance (MEM) is a department which the tasks are repairing, maintaining and performing preventive maintenance for heavy equipment, such as haulmaster and excavators. In the process of repairing and maintaining heavy equipment, a mechanic has higher risk for suffering MSDs because the work was mostly done manual handling so that the working positions, such as standing, turning, bending and lifting loads, were done repeatedly in a long term of time. Musculoskeletal disorder is a musculoskeletal system disorder characterized by decreased function of the parts of the human body, such as the muscles, tendons, skeleton, ligaments, nerves, joints, cartilage, bone, and blood vessels of the hands, feet, head, neck and back. The aim of this research was to determine the relationship between individual characteristics and occupational factors on the incidence of MSDs experienced by workers. The research data was obtained using questionnaires and interviews which involved 22 mechanical workers at MEM PT Vale Indonesia. The results showed that 11 respondents were aged 35 years (50%), the respondents mostly have 4 years of service life (86.4%), 20 respondents (90.9%) did not do exercise, 11 respondents (50 %) have smoking habits, the most of respondents have higher risk categories of jobs (67%), and 11 workers (50%) experiencing MSDs symptoms. The results of analysis using the chi-square test showed that age, smoking habit and occupational factors were related with the onset of MSDs symptoms experienced by workers, while the working period and exercise habits were not related to the MSDs symptoms. So the advices that can be given to the company are implementing the regulations about smoking prohibition, intervening the ergonomics by providing back-support for workers, design the job rotation, held a morning exercise activities in order to minimize MSDs symptoms and medical examination related to the skeletal muscle condition.Keyword: musculoskeletal disorder,